2021
DOI: 10.3389/fphar.2021.754527
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilatory Effect of Guanxinning Tablet on Rabbit Thoracic Aorta is Modulated by Both Endothelium-Dependent and -Independent Mechanism

Abstract: Vasodilatory therapy plays an important role in the treatment of cardiovascular diseases, especially hypertension and coronary heart disease. Previous research found that Guanxinning tablet (GXNT), a traditional Chinese compound preparation composed of Salvia miltiorrhiza (Danshen) and Ligusticum chuanxiong (Chuanxiong), increase blood flow in the arteries, but whether vasodilation plays a role in this effect remains unclear. Here, we found that GXNT significantly alleviated the vasoconstriction of isolated ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…GXNT is clinically used for treating CHD and ischemic cardiomyopathy with significant curative effects [13]. Our previous pharmacological experiments confirmed that GXNT has the functions of reducing whole blood viscosity, improving blood rheology abnormalities, antimyocardial ischemia, antithrombosis, and vasodilation [14][15][16][17][18][19]. In this study, we established a CA model induced by a HF diet in Tibetan minipigs and simultaneously interfered with GXNT.…”
Section: Discussionmentioning
confidence: 97%
“…GXNT is clinically used for treating CHD and ischemic cardiomyopathy with significant curative effects [13]. Our previous pharmacological experiments confirmed that GXNT has the functions of reducing whole blood viscosity, improving blood rheology abnormalities, antimyocardial ischemia, antithrombosis, and vasodilation [14][15][16][17][18][19]. In this study, we established a CA model induced by a HF diet in Tibetan minipigs and simultaneously interfered with GXNT.…”
Section: Discussionmentioning
confidence: 97%
“…[ 10 ] Yun Ling et al found that opening of calcium and potassium channels in vascular smooth muscle cells (VSMCs) and activation of CaMKII/eNOS signaling pathway in vascular endothelial cells were significant mechanisms by which GXNT facilitated vasodilation. [ 11 ] The promotion of angiogenesis is a potential effect of GXNT observed in a study, which suggest that this may be due to the interaction between Salvianolic acid B and ferulic acid. [ 12 ] GXNT treatment can promote the restoration of various blood lipid indices as well as levels of VEGF, ET-1, and NO, thereby contributing to the protection of vascular endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…DGS was composed of three Chinese medicinal materials, namely, Salviae Miltiorrhizae Radix et Rhizoma (Danshen), Puerariae Lobatae Radix (Gegen), and Crataegi Folium (Shanzhaye). Modern pharmacological studies have shown that Danshen can increase blood flow [9], improve circulation [10], and preserve endothelial function [11]. Danshen is the most representative herbal medicine in the Chinese medicine formula repertoire for the treatment of ischemic diseases [12].…”
Section: Introductionmentioning
confidence: 99%